Heliosystem of Auxiliary Heat Supply for a Mining Enterprise - Shkrylova S.; Kostenko V.; Skrynetska I. (Журнал інженерних наук)
In the conditions of the global ecological crisis in the world and Ukraine, the issue of finding alternative energy sources becomes relevant. One of the most common types of renewable energy is solar energy. In Ukraine today, the most promising direction of using solar energy is its direct transformation into low-potential thermal energy. To get electric power, solar radiation is the mere alternative to electric power generated from mined fuel, and without the pollution of air and water, or adverse consequences manifested in global warming. The disadvantage of this type of installation is the limitation of the duration of light time, as well as the effect of cloudiness. During the day, the number of solar radiation changes, to stabilize it is necessary to accumulate and accumulate it for further use, the technical implementation of stable operation of solar installation due to the use of terrestrial radiation and the accumulator of a specific part of solar energy is proposed. The purpose of the work is experimental studies to ensure the stable operation of the solar collector under cloudy conditions. The paper is aimed at the stabilization of the operation of the solar installation and to obtain additional heat after the Sun’s cloud cover. The use of a solar thermal collector is advisable in solar heating and hot water systems in conditions of alternating solar radiation. The results of physical modeling have proved the efficiency of the method of combining types of thermal radiation, due to the accumulation of energy it is possible to increase the quantitative index of solar energy in the conditions of cloudiness by 3 times.